Evaluation of the impact of lean construction implementation on efficiency and waste management in large-scale infrastructure projects - Riyanti, Eva; Kurniawan, Pramudya; Haryani, Susi; Haffiyan, Qalbi; Rizal, Rizal (International research journal of management, IT and social sciences, 2025)
This study aims to evaluate the impact of Lean Construction implementation on efficiency and waste management in large-scale infrastructure projects through a literature review. Lean Construction, adapted from lean manufacturing principles, offers a systematic strategy to reduce waste, improve collaboration, and optimise workflows. The synthesis of various studies indicates that the application of Lean Construction can improve project time efficiency by up to 25% and reduce costs by 18–30%, primarily through the reduction of waste types such as defects, overproduction, inventory, and waiting. However, implementation on projects with multiple stakeholders still faces challenges such as fragmented coordination, resistance to cultural change, and misalignment of contract systems. Strategic solutions identified include redesigning collaborative contracts, integrated human resource training, and leveraging digital technology for cross-disciplinary data synchronisation. This study recommends the need for synergy between the government, industry, and academia to create a more efficient and sustainable construction ecosystem in Indonesia.